Pengelolaan Sampah Organik dan Anorganik Untuk Meningkatkan Nilai Guna Dan Pendidikan Karakter Siswa Di Sekolah Dasar - Dedi Miswar; Wanda Hamidah; Anis Nurul Laili; Resa Deadara; As' ari; Rizkia Pangestika; Dina Nasha Sekar; Firda Reza Aryatina; Anisa Cahya Putri; Muhammad Nanang Fatoni; Putri Pertiwi; Chaterine Pratami Putri (CV. Multi Kreasi Media, 2024)
Waste is the remains of daily human activities from natural processes in solid form. Waste needs to be managed well so as not to damage the environment. The aim of this community service activity is (1) to provide knowledge to students at SD 1 Tanjung Senang, BandarLampung City about how waste can pollute the environment. (2) provide skills to students that waste is differentiated into several types. (3) Give students skills to process inorganic wasteecobrik useful value (4) Increasing students' creativity in processing inorganic waste into ecobricks and hand washing soap from used cooking oil (inorganic). The method used is this: 1) Lecture and discussion about waste. 2). Training on sorting waste, 3) Training on processing organic and inorganic waste into ecobricks and hand washing soap from used cooking oil (inorganic). The result of this community service activity is that it has increased the knowledge of students and teachers in the Tanjung Senang Elementary School, Bandar Lampung City regarding waste, improved skills in how to differentiate types of waste, been able to process waste into goods of use value, and increased creativity in processing plastic waste into ecobriks. . Conclusion: Community service activities for students at SD Negeri 1 Tanjung Senang increase knowledge about waste, how to manage it and provide character education for students.